Technical and Economic Assessment of PV Resource Based DC and AC Connected Behind the Meter System for Residential Load - Aftab, Khan Huma; Yaseen, Mohd. Yusuf; Asim, Mohammed (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Electric-energy storage using the behind-the-meter system is presently considered as a beneficial scheme of providing renewable energy to the grid. Presently mandates are introduced and subsidies are proposed for adoption of such systems in various countries. In this work solar photovoltaics (PV) array with behind the-meter storage is taken under consideration and presenting an analysis of the benefit of systems installed by customer in Lucknow, U.P, India. Variety of dispatch strategies, including automated peak-shaving & manual scheduling are investigated for determining the best mode to use for the system of energy storage that helps in increasing the value of system and mitigating the demand charges. Recent ongoing electric tariffs, and site-specific load and weather database are integrated for performing a accurate analysis by utilizing the open access, publicly available tool known as System Advisor Model (SAM). It has been found that installation of PV structures with a lithium-ion battery system capable to yields positive net-present values with consideration of high demand charge utility rate structures and dispatching the batteries utilization under day-ahead forecasting. Conclusions about influential factors to determine the net present value considered that shows high sensitivity of economics of battery to the combination with system parameters at specific location.